Buying the cow - Becker, Walt; Nelson, Peter (Culver City, California Columbia/Tristar Home Entertainment, 2000)
David (O'Connell) is informed by his girlfriend of five years Sarah (Wilson) that she is leaving for New York for two months in order for him to decide whether he is ready to marry her. Seeking advice from his wacky, womanizing best friends (Reynolds and Bellamy) David begins to navigate the treacherous Los Angeles singles scene until fate intervenes and he falls for a mystery woman! Sarah meanwhile gets an offer from her handsome boss that she may not be able to refuse. David's search for what he thinks might be his true love triggers memories of a girl fro his past that figures into the lives of all the characters, with some wildly unexpected results!
Executive producers, Barry London, Brent Baum, Brad Jenkel.
Jerry O'Connell, Bridgette Wilson, Alyssa Milano, RYan Reynolds, Annabeth Gish.
Dolby digital.
In English.